2019
DOI: 10.1002/macp.201800571
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylic Acid‐Based Coordination Supramolecular Elastomer with High Strength, Excellent Fatigue‐Resistance, and Self‐Recovery Properties

Abstract: Supramolecular elastomers have attracted extensive attention due to their excellent mechanical properties. Herein, inspired by the concept of a dual cross‐linked network structure, a dual‐component coordination supramolecular elastomer is prepared via photopolymerization of three monomers combined with zinc ion (Zn2+)‐crosslinked low molecular weight polyacrylic acid (PAA). The covalent network of three monomers serves as a soft component forming the supporting network. The network of Zn2+ crosslinked low mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The underlying mechanism for toughness and stiffness improvement in the iron‐treated network is the stress‐responsive and transient nature of the ionic nanoaggregates. After that, ionic interactions such as zinc‐imidazole complex, Zn 2+ /COO − metal‐ligand, copper‐cellulose paper, iron‐epoxy coordination, Fe 3+ and Ca 2+ /OH complex, and silver‐NH 2 /COOH coordination were introduced into rubber elastomer and hydrogel, respectively, to prepare high toughness materials. Given all that significant progress has been made in the elastomer area, it is expected to apply this toughening strategy for the stiff structural materials, like densely cross‐linked epoxy resins.…”
Section: Viscosity and Refractive Index Of All K‐pamsmentioning
confidence: 99%
“…The underlying mechanism for toughness and stiffness improvement in the iron‐treated network is the stress‐responsive and transient nature of the ionic nanoaggregates. After that, ionic interactions such as zinc‐imidazole complex, Zn 2+ /COO − metal‐ligand, copper‐cellulose paper, iron‐epoxy coordination, Fe 3+ and Ca 2+ /OH complex, and silver‐NH 2 /COOH coordination were introduced into rubber elastomer and hydrogel, respectively, to prepare high toughness materials. Given all that significant progress has been made in the elastomer area, it is expected to apply this toughening strategy for the stiff structural materials, like densely cross‐linked epoxy resins.…”
Section: Viscosity and Refractive Index Of All K‐pamsmentioning
confidence: 99%
“…In order to better understand the effect of this design on the improvement of the comprehensive mechanical properties of materials, we compare the fracture energy improving efficiency (the fracture energy of the PI-PHEA RC elastomer over that of the linear copolymer) of this study with dates of tough elastomers reported in recent literatures. The strength, strain, and toughness of the PI-PHEA RC elastomer (9.79 MPa, 887%, 43.4 MJ/m 3 ) are 6.4 times, 1.25 times, and 8.3 times that of the linear copolymer (1.52 MPa, 727%, 5.27 MJ/m 3 ), respectively (Table ), and the fracture energy improving efficiency is significantly higher than that of most other methods ,,, As shown in Figure , only one article got better fracture energy improvement efficiency than ours . That work developed an ultrastrong and highly stretchable polyurethane elastomer by introducing a zipper-like ring-sliding structure to the materials.…”
Section: Resultsmentioning
confidence: 64%